Evaluation of the social, clinical and laboratorial profile of patients diagnosed with leprosy in a reference center in São Paulo - Ana Carolina Souza Porto; Renata Borges Fortes Costa Figueira; Jaison Antônio Barreto; José Roberto Pereira Lauris (Sociedade Brasileira de Dermatologia, 2015)
BACKGROUND: Leprosy is the main infectious cause of disability. It is said to be eradicated in São Paulo since 2005, but diagnosis is still late. OBJECTIVES: To investigate the social, clinical and laboratorial profile of leprosy patients diagnosed between 01/2007 and 12/2011, in a reference center in São Paulo. METHODS: Retrospective descriptive study. Data of all new leprosy cases diagnosed between 01/2007 and 12/2011 were raised in São Paulo. RESULTS: 103 men and 71 women were diagnosed, most of them were multibacillary. Mean age at diagnosis was 49 yrs; 2,2% were children; 70% had incomplete primary education; 50% were referred without diagnostic suspicion of leprosy. Mean time since first symptoms/signs and diagnosis was 2 years; 64% of patients had some degree of disability, and 26% had grade 2. 23 cases were diagnosed only after being summoned, and 80% of these had no disability. Agreement between the Ridley and Jopling and the WHO classification was 75% (kappa index = 0.44). Serology for IgM anti-PGL1 (87 patients) showed a mean value of 0.25, and an association between MB classification and test positivity (p <0.001). CONCLUSIONS: Leprosy diagnosis in São Paulo is late. The disease mainly affected the socially disadvantaged and economically active population. Failure to detect the disease (41% in the last 10 years) could be due to the lack of suspicion and to decentralization. For the classification of patients with advanced leprosy, both the WHO and R&J classifications proved to be helpful tools.